International Scientific Conference of the Vilnius University “With Eagle and “Vytis” Signs. Polish-Lithuanian Scientific and Cultural Relations in the History of Vilnius University” - Fedorovič, Irena; Geben, Kinga (Slavistica Vilnensis, 2019)
International Scientific Conference of the Vilnius University “With Eagle and “Vytis” Signs. Polish-Lithuanian Scientific and Cultural Relations in the History of Vilnius University” (Vilnius, November 21th–22th, 2019)
Keywords: none